2011
DOI: 10.1111/j.1532-5415.2011.03785.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Outcomes and the Use of Multimodality Therapy in Young and Elderly People Undergoing Surgical Resection of Pancreatic Cancer

Abstract: Carefully selected elderly individuals experience similar perioperative outcomes and overall survival to those of younger individuals after resection of pancreatic cancer. There appears to be a significant disparity in the use of adjuvant therapy between young and elderly individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 41 publications
1
43
0
1
Order By: Relevance
“…Outcomes of various surgical procedures, including PD, in the older population, have become a subject of concern; however, limited data exist [4, 712, 17]. It has been well established in previous studies that PD could safely be performed for patients aged 70 years or older.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Outcomes of various surgical procedures, including PD, in the older population, have become a subject of concern; however, limited data exist [4, 712, 17]. It has been well established in previous studies that PD could safely be performed for patients aged 70 years or older.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies have reported age to be a risk factor in postoperative morbidity after pancreatic resection [6, 11, 1316], while others reported that increased age alone does not prohibit pancreatic surgery [7, 10, 12, 17]. Recently, Lee et al reported that increased age is not a risk factor for postoperative mortality based on information from the American College of Surgeons National Surgical Quality Improvement Program (NSQIP) database [3].…”
Section: Introductionmentioning
confidence: 99%
“…Other institutional studies have been hampered by small sample sizes and wide-ranging criteria of what constitutes an elderly population. 3,[25][26][27][28] In addition, single-center results may not be generalizable to institutions that are not specialized pancreatic surgery centers. In contrast, our analysis contains data from a large, multiple-institution, heterogeneous patient pool (923 PDs done in patients 80 years).…”
Section: Discussionmentioning
confidence: 99%
“…Although these initially began as classroom interactions, they now commonly extend into the clinical arena, which we believe will have a positive impact in improving the care of elderly surgical patients in our hospital. Moreover, there has been a global increase in resident interest in geriatric surgery research, and several residents have performed clinical outcomes studies in the geriatric population and successfully published their work (Barbas et al, 2012;Reddy et al, 2011;Speicher, Lagoo-Deenadayalan, Galanos, Pappas, & Scarborough, 2013).…”
Section: Discussionmentioning
confidence: 99%